Implementasi Pendekatan PDIA untuk Meningkatkan Hasil Belajar pada Pembelajaran Programmable Logic Controller - Mohamad Syamsul Huda; Puput Wanarti Rusimamto; Luthfiyah Nurlaela; Rommy Mochamad Ramdhani; I.G.P. Asto Buditjahjanto (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to improve learning outcomes in the Programmable Logic Controller (PLC) subject through the application of the Problem Driven Iterative Adaptation (PDIA) approach to class XI students of Electrical Power Installation Engineering at SMK KAL-1 Surabaya. The study used a Classroom Action Research design integrated with PDIA stages, including initial problem analysis, action planning, implementation, reflection, and continuous adaptation. The study was conducted in two cycles with 35 students as subjects. The research instruments included knowledge tests, practical skills assessments, and student activity observation sheets. Data were analyzed descriptively quantitatively and qualitatively. The results showed an increase in learning outcomes in the domains of knowledge and practical skills. The average knowledge score increased from 75.23 in cycle I to 78.30 in cycle II, while the practical skills score increased from 76.33 to 80.26. Student learning completeness also increased until all students reached the Minimum Completeness Criteria in cycle II. In addition to improving learning outcomes, the application of PDIA encouraged students to be more active, reflective, and involved in solving PLC programming problems. These findings demonstrate that the PDIA approach effectively creates PLC learning that is adaptive, contextual, and responsive to the dynamics of student learning difficulties in vocational education. This approach offers practical implications for vocational teachers in designing learning strategies based on real-world industrial problems and strengthening students' critical thinking and technical problem-solving skills in a sustainable and measurable manner in the vocational school context.